The Influence of the Effectiveness of Good Corporate Governance and Disclosure of Corporate Social Responsibility on Tax Avoidance and its Impact on Company Value (Study Of Coal Sector Mining Companies Listed On The Indonesia Stock Exchange For The 2015-2019 Period) - SARI, Intan; DAITO, Apollo (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to determine the effect of good corporate Governance and corporate social responsibility on tax avoidance and their impact on firm value. This study uses a sample of the Indonesia Stock Exchange for the 2015-2019. The type of data used in this research is secondary data. The results showed that the mechanism of good corporate Governance has an effect on tax avoidance, disclosure of corporate social responsibility has no effect on tax avoidance, the mechanism of good corporate Governance has an effect on firm value, Disclosure of Corporate Social Responsibility has no effect on firm value, Tax Avoidance has a significant effect on firm value in Coal Sector Mining Company Listed on the Indonesia Stock Exchange. Good Corporate Governance positively impacts tax avoidance in small companies, strengthening relationships between shareholders, managers and employees. Disclosure of Corporate Social Responsibility (CSR) influences tax avoidance, but not for large companies that carefully report their finances to benefit stakeholders. CSR is considered a moral obligation, forming the character of an honest manager. Good Corporate Governance also contributes to increasing company value through its mechanisms. However, CSR disclosure does not affect company value. At the same time, high tax avoidance positively impacts company value, reflects profits and gets a positive response from investors in making investment decisions.